A Giant Bulla of the Lung Mimicking Hydro-pneumothorax with Contra Lateral Mediastenal Shifting (Journal of Medicine, 2014)
Herein, we report a case of giant bulla of the left lung in a 35 years old woman mimicking tension puemothorax.Based on initial clinico-radiological parameters, she was treated with intercostal tube drain and as her condition did not improve after chest tube insertion, she was referred to our centre. Computed tomography of thorax was done and it was reported to be a large hydropeumothorax causing compression collapse of left lung .We decided to plan for thoracotomy and it was revealed a large bulla arising from left lower lobe which was resected with significant radiological recovery. Giant bulla should be included in the differential diagnosis of pneumothorax.DOI: http://dx.doi.org/10.3329/jom.v15i1.19871 J Medicine 2014; 15: 48-50